Foundation Scholars Decision Support System with Simple Additive Weighting - Sundari Retno Andani; Sumarlin, Sumarlin (Yayasan Literasi Sains Indonesia, 2023)
Scholarships are one of the solutions in dealing with dropping out of school to increase the quantity of human resources in Indonesia. There are various types of scholarships given to outstanding students, one of which is a foundation scholarship. Foundation scholarships are scholarships whose funding comes from higher education foundations intended for outstanding and economically disadvantaged students. A decision support system (SPK) is needed in determining foundation scholarship recipients. With SPK, the results obtained are more objective based on the criteria used, accurate, effective and efficient. The SPK method used in this study is the Simple Additive Weighting (SAW) method. The SAW method performs a search with a weighted sum of performance ratings for each alternative on all criteria. The criteria used in this study are the Grade Point Average (GPA), parents' income and the number of dependents. Calculations using the SAW method will produce weight values, criteria, alternatives and ranking results of scholarship recipients as material for decision making.